The role of patient primary language in access to brain tumor resection: Evaluating emergent admission and hospital volume. (December 2021) - Witt, Emily E.; Eruchalu, Chukwuma N.; Dey, Tanujit; Bates, David W.; Goodwin, C. Rory; Ortega, Gezzer
Highlights: Patient primary language affects access to timely surgical care for brain tumors. Non-English/Non-Spanish speakers are twice as likely to be admitted emergently. Primary Spanish speakers are less likely to be admitted to high-volume centers. Factors other than language explain access to high-volume centers. Abstract: Background: This study investigated the effect of limited English proficiency on access to neuro-oncologic surgery. We compared rates of emergent/urgent admission and admission to high-volume hospitals for English and non-English primary language patients with brain neoplasms. Methods: Using the AHRQ-HCUP New Jersey State Inpatient Database, we included patients 18–90 years old who underwent resection of a supratentorial primary brain tumor (PBT), meningioma (MA) or brain metastasis (BM) from 2009–2017. Outcomes were emergent/urgent admission and annual hospital procedure volume. Univariable and multivariable analyses compared Spanish (SPL), Non-English Non-Spanish (NENS), and English (EPL) primary language groups. Results: 7, 402 patients were included: 2, 996 PBT, 2, 115 MA, and 2, 291 BM. SPL patients (n = 300) were younger and had a greater proportion of non-commercially insured, low-income patients with lower comorbidity scores. NENS patients (n = 260) had similar age and comorbidity scores as EPL patients, but a greater proportion had non-commercial insurance and low income (p < 0.001). Multivariable analysis revealed NENS, but not SPL, patients had increased odds of emergent/urgent admission (2.10(1.50−2.93), p < 0.001), but demonstrated no association between admission to higher volume centers and primary language. Conclusion: Patient primary language may influence access to timely neurosurgical care, but access to high-volume centers appears to be mediated by other factors. Policy summary statement: In addition to efforts to improve health care access for patients with limited English proficiency, multilingual health literacy and patient education interventions may help to promote timely presentation for brain tumor resection among this vulnerable patient population.